2017
DOI: 10.1002/ejoc.201700689
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanochemical‐Assisted Oxidation of Amines to Carbonyl Compounds and Nitriles

Abstract: A mild, efficient, metal‐ and solvent‐free oxidation of primary amines to aldehydes, ketones, and nitriles under ball‐milling conditions is presented. This method has proved to be compatible with various functional groups and only requires easily accessible starting materials. Simple purification of the reaction mixtures by short‐column chromatography afforded pure aldehydes, ketones, and nitriles as products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…This selectivity is in contrast with other oxidizing agents used in earlier reports. [3][4][5][6][7][8][9][10][11] Isobutyl-methylamine also well reacted under identical conditions to provide corresponding isobutyraldehyde 2o in excellent yield of 89% (Scheme 3). Oxidation of symmetrical amines such as dibenzylamine using PhI(OAc) 2 (1 equiv) and TEMPO (0.1 equiv) in dry CH 2 Cl 2 provided the mixture of benzaldehyde (2b) and benzyl amine (1b) in 1 : 1 ratio in the good yield of 90% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This selectivity is in contrast with other oxidizing agents used in earlier reports. [3][4][5][6][7][8][9][10][11] Isobutyl-methylamine also well reacted under identical conditions to provide corresponding isobutyraldehyde 2o in excellent yield of 89% (Scheme 3). Oxidation of symmetrical amines such as dibenzylamine using PhI(OAc) 2 (1 equiv) and TEMPO (0.1 equiv) in dry CH 2 Cl 2 provided the mixture of benzaldehyde (2b) and benzyl amine (1b) in 1 : 1 ratio in the good yield of 90% yield.…”
Section: Resultsmentioning
confidence: 99%
“…These two methods required harsh reaction conditions and an extra hydrolysis step to access the target carbonyl compound (eqn (2), Scheme 1). 10,11 In continuation of our interest in development of new methodologies using PhI(OAc) 2 12 and to address issues associated with existing protocols for the conversion of amines to carbonyl compounds, herein we report an efficient, rapid, mild, metal free and environment friendly protocol involving nonmetallic, less toxic and affordable hypervalent iodine (PhI(OAc) 2 ) in combination with TEMPO as an oxidizing agent for the rst time without any external oxygen source (eqn (3), Scheme 1). 13,14 Hypervalent iodine compounds such as (diacetoxyiodo) benzene (PhI(OAc) 2 ), [bis(triuoroacetoxy)] benzene…”
Section: Introductionmentioning
confidence: 99%
“…In order to optimize all the experimental conditions, we fine-tuned the reaction by using 3-phenyl-1-propanol as a model reagent and N -chlorosuccinimide (NCS) as an oxidizing agent. NCS is one of the most widely used co-oxidizing reagents in homogeneous-phase TEMPO-assisted oxidation reactions and, we have gained valuable experience in handling this reagent in several mechanochemical applications [4546].…”
Section: Resultsmentioning
confidence: 99%
“…25 Using metal-free oxidants, Gaspa et al reported a mild and solvent-free oxidation of primary amines to aldehydes, ketones, and nitriles by N-chlorosuccinimide under ballmilling conditions. 26 Very recently Brisar et al described the use of pyrazine cation for the aerobic oxidation of amines to imines. 27 Concerning the use of inorganic metal-free oxidants, choline peroxydisulfate was successfully applied to a selective oxidation of secondary amines to hydroxylamines.…”
Section: Introductionmentioning
confidence: 99%